Color and texture associations in voice-induced synesthesia - Moos, Anja; Simmons, David; Simner, Julia; Smith, Rachel (Frontiers in Psychology, 2013)
Voice-induced synaesthesia, a form of synaesthesia in which synaesthetic perceptions are induced by the sounds of people’s voices, appears to be relatively rare and has not been systematically studied. In this study we investigated the synaesthetic colour and visual texture perceptions experienced in response to different types of “voice quality” (e.g. nasal, whisper, falsetto). Experiences of three different groups – self-reported voice synaesthetes, phoneticians and controls – were compared using both qualitative and quantitative analysis in a study conducted online. Whilst, in the qualitative analysis, synaesthetes used more colour and texture terms to describe voices than either phoneticians or controls, only weak differences, and many similarities, between groups were found in the quantitative analysis. Notable consistent results between groups were the matching of higher speech fundamental frequencies with lighter and redder colours, the matching of “whispery” voices with smoke-like textures and the matching of “harsh” and “creaky” voices with textures resembling dry cracked soil. These data are discussed in the light of current thinking about definitions and categorizations of synaesthesia, especially in cases where individuals apparently have a range of different synaesthetic inducers.